(3cJGH HGddZI GdJQcjIs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje (B" (3QHfG dG JRZ bdhHfG HYO EP gOjJfG hgH dfG ef dOfc QMeI Efc CfJ GdhgGH QHfG Efc LGeY GdfGS djhe dG QjH ajg Ef Gddg dG jNda GdejYGO (B" (3SjGS BaQ jO cGQi s
(3BNQgG (B:s
(3bGHd EUdGM HGTO HLGi ChQfOG hGddg hdi GdJhajb SHMGf QHc QH GdYRI YeG jUahf hSdGe hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdcJGH ecJhH HGddZI GdJQcjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs